PLANNING FOR WASTE COLLECTION AND STORAGE IN NGEPUNG VILLAGE, KEDAMEAN DISTRICT, GRESIK - Andika Putra; Yusrianti Yusrianti; Shinfi Wazna A. (Universitas Lambung Mangkurat, 2021)
Ngepung Village is a village located in the eastern part of Kedamean District, Gresik Regency with an area of 5.08 km2. Ngepung Village is divided into 3 Hamlets, 5 Rukun Warga (RW), and 14 Rukun Tetangga (RT) consisting of 3493 people. Waste management in Ngepung Village still uses the old paradigm, namely gathering-burning or gathering-wasting. The purpose of this study is to determine the existing condition of waste management in Ngepung Village and to plan waste collection and storage. The research method includes direct measurement of waste generation, interviews, observation and documentation. Determination of sampling using simple random sampling according to SNI 19-3964-1994. Data analysis used quantitative descriptive techniques. The results of the study stated that most of the residents of Ngepung Village used plastic bags as garbage containers. The average value of waste generation in Ngepung Village is 2.05 L/org.day or 0.31 kg/org.day. Meanwhile, the composition of waste is dominated by organic waste of 60.49%. The waste collection plan consists of 2 types of waste containers, namely organic and inorganic containers, with a housing waste container capacity of 25 liters per family, a 70 liter office waste container capacity, 100 liter pesantren waste containers, 30 liter schools, and 25 liter places of worship. Garbage collection is planned to be carried out every 3 days with 3 cycles using 5 units of three-wheeled motorized carts with a capacity of 1.25 m3.